1997
DOI: 10.1002/hlca.19970800112
|View full text |Cite
|
Sign up to set email alerts
|

6‐Azabicyclo[3.1.0]hex‐30‐en‐2‐ol Derivative, photochemically generated building blocks for bicyclic β‐lactams

Abstract: The title compounds 4 are obtained by photolysis of simple N‐alkylpyridinium salts in H2O or alcohol. On reaction with [Fe2(CO)9] in THF, 4 gives bicyclic tricarbonyliron complexes 13a–d, which on oxidative decomplexation with ceric ammonium nitrate afford cis‐fused cyclopenteno‐β‐lactams 15a–d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…These particular substrates engaged very efficiently in β-lactam formation under the action of diiron nonacarbonyl. In this field, Ley [71] showed that aziridine 97 can be treated with Co 2 (CO) 8 The vinylaziridine motif can be embedded in a bicyclic structure 101 as reported by Burger [72]. In this case, final iron decomplexation from 102 was performed with cerium ammonium nitrate to give β-lactam 103 in good yield (Scheme 25).…”
Section: Expansion Into Azetidines and Azetidinonesmentioning
confidence: 85%
“…These particular substrates engaged very efficiently in β-lactam formation under the action of diiron nonacarbonyl. In this field, Ley [71] showed that aziridine 97 can be treated with Co 2 (CO) 8 The vinylaziridine motif can be embedded in a bicyclic structure 101 as reported by Burger [72]. In this case, final iron decomplexation from 102 was performed with cerium ammonium nitrate to give β-lactam 103 in good yield (Scheme 25).…”
Section: Expansion Into Azetidines and Azetidinonesmentioning
confidence: 85%
“…Deuterium labeling experiments : For practical reasons, 3,4,5‐trideuterio‐ N ‐(3‐hydroxypropyl)pyridinium chloride ([D 3 ] 1 b ) was chosen for the reinvestigation of labeling experiments (Scheme ). The aziridine [D 3 ] 2 b that results from its photohydration at λ =254 nm is considerably more stable and less prone to Grob fragmentation2 than the N ‐methyl derivative used in the original work of Wilzbach et al1 Integration of the 1 H NMR spectrum of the isolated product [D 3 ] 2 b recorded at 500 MHz in CD 3 OD provided the relative proton distribution over the five ring positions as given in Table 3. The assignment of the resonances was unambiguously established by a 13 C, 13 C INADEQUATE‐2D experiment25 combined with the appropriate 1 H/ 13 C correlation.…”
Section: Resultsmentioning
confidence: 99%
“…In 1972, Kaplan, Pavlik, and Wilzbach1 showed that the irradiation of N ‐methylpyridinium chloride ( 1 a ) in H 2 O in the presence of base gave the bicyclic aziridine (±)‐ 2 a (Scheme ). Their communication went relatively unnoticed for nearly a quarter of a century until it was recognized that this transformation of the pyridinium ring provides a new and powerful approach to aminocyclopentanes with well‐defined substitution patterns 2, 7. Highly functionalized aminocyclopentanes are of considerable interest as precursors of glycosidase inhibitors8 and of carbocyclic analogues of nucleosides 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The pyridine species were quaternised by heating in neat alkyl bromide or iodide inside a sealed tube and, after filtration, the pyridinium halides 13 were converted to the tetrafluoroborate salts 14 using silver carbonate and fluoroboric acid. Chloride 6,8,9 and perchlorate 7 salts have previously been used for photosolvolysis reactions, although we opted to use tetrafluoroborate salts; they were easy to make from the halide salt (which tended to undergo photoinduced charge transfer reactions) and were less likely to detonate than perchlorate salts.…”
Section: Methodsmentioning
confidence: 99%